Urinary Bisphenol A Levels in Young Men: Association with Reproductive Hormones and Semen Quality - Lassen, Tina Harmer (NLM-Export, 2014)
Background: Few human studies have examined bisphenol A (BPA) exposure in relation to semen quality and reproductive hormones in men, and results are divergent. Objectives: We examined associations between urinary BPA concentration and reproductive hormones, as well as semen quality, in young men from the general population. Methods: Our study population consisted of 308 young men from the general population. Urinary BPA concentration was measured by isotope dilution TurboFlow-liquid chromatography–tandem mass spectrometry. We used multiple linear regression analysis to estimate associations between BPA concentration and reproductive hormones and semen quality, adjusting for confounding factors. Results: We found that 98% of the men had detectable urinary levels of BPA. Median (5th–95th percentiles) BPA concentration was 3.25 ng/mL (0.59–14.89 ng/mL). Men with BPA concentrations above the lowest quartile had higher concentrations of serum testosterone, luteinizing hormone (LH), estradiol, and free testosterone compared with the lowest quartile (p(trend) ≤ 0.02). Men in the highest quartile of BPA excretion had on average 18% higher total testosterone (95% CI: 8, 28%), 22% higher LH (95% CI: 6, 39%), and 13% higher estradiol (95% CI: 4, 24%) compared with lowest quartile. Men in the highest quartile of BPA also had significantly lower percentage progressive motile spermatozoa compared with men in the lowest quartile (–6.7 percentage points, 95% CI: –11.76, –1.63). BPA was not associated with other semen parameters. Adjusting for dietary patterns did not influence the results. Conclusions: The pattern of associations between BPA and reproductive hormones could indicate an antiandrogenic or antiestrogenic effect, or both, of BPA on the hypothalamic–pituitary–gonadal hormone feedback system, possibly through a competitive inhibition at the receptor level. However, additional research is needed to confirm our findings and to further test the suggested potential mechanisms. Citation: Lassen TH, Frederiksen H, Jensen TK, Petersen JH, Joensen UN, Main KM, Skakkebaek NE, Juul A, Jørgensen N, Andersson AM. 2014. Urinary bisphenol A levels in young men: association with reproductive hormones and semen quality. Environ Health Perspect 122:478–484; http://dx.doi.org/10.1289/ehp.1307309